Geomagnetic Pulsations Driving Geomagnetically Induced Currents. Issue 2 (2nd February 2021) - Heyns, M. J.; Lotz, S. I.; Gaunt, C. T.
Abstract: Geomagnetically induced currents (GICs) are driven by the geoelectric field induced by fluctuations of Earth's magnetic field. Drivers of intense GICs are often associated with large impulsive events such as coronal mass ejections. To a lesser extent fluctuations from regular oscillations of the geomagnetic field, or geomagnetic pulsations, have also been identified as possible drivers of GICs. In this work we show that these low‐frequency pulsations are directly observed in measured GIC data from power networks. Due to the low‐pass nature of GICs, Pc5 and lower‐frequency pulsations drive significant GICs for an extended duration even at midlatitudes. Longer‐period Ps6‐type disturbances apparently not typical of midlatitudes are seen with GIC amplitudes comparable to the peak GIC at storm sudden commencement. The quasi‐ac (alternating current) nature of the sustained pulsation driving affects the power system response and cannot be properly modeled using only direct current (dc) models. A further consideration is that the often used d B / d t GIC proxy is biased to the sampling rate of the geomagnetic field measurements used. The d B / d t metric does not adequately characterize GIC activity at frequencies in the low ultralow‐frequency (ULF) range, and a frequency‐weighted proxy akin to geoelectric field should be used instead. Plain Language Summary: Geomagnetically induced currents (GICs) are naturally occurring currents induced in conductive media, such as the Earth, by fluctuations of the geomagnetic field. When large grounded conductors such as power networks are present, these currents also enter the network and pose serious risk to the stability of the network. In extreme cases, the GICs can result in total network collapse. Particular fluctuations of the local geomagnetic field are geomagnetic pulsations, which occur when the magnetic field lines are perturbed and ring, causing oscillations. These oscillations have not previously been thought to be effective in driving large GICs, but now measured GIC data have shown this is not always the case, and the power grid couples particularly well to low‐frequency pulsations. Essentially, the power grid acts as an antenna, and pulsations have been picked up where not previously expected. Understanding the effectiveness of these pulsations and including them in GIC modeling is vital for protection of the grounded power networks we rely on. Key Points: Low‐frequency geomagnetic pulsations couple effectively to GICs and need to be taken into account in modeling power network response Ps6‐type disturbances along with other pulsations are seen at midlatitudes during intense storms and can drive significant GICs d B / d t may not be an appropriate GIC proxy given pulsation driving